Father-daughter interactional patterns associated with adolescent depression: An examination of attachment and communication within the dyad - Demidenko, Natasha (University of Ottawa (Canada), 2007)
The present study was designed to examine the links between father-daughter attachment, paternal acceptance and rejection, emotional availability (EA), adolescents' affective perception of parents, and the quality of father-daughter communication in adolescents with and without depression, taking into consideration paternal general psychopathology and maternal mood disorder. Fifty-one adolescent girls diagnosed with a depressive disorder (CDA) and 65 never-depressed girls (NDA), ages 13 to 19, and their fathers, completed semi-structured diagnostic interviews and measures of parent-adolescent attachment and communication. Mothers completed a diagnostic interview for mood disorders. In the first manuscript, we found that girls in the CDA group were more likely than those in the NDA group to have fathers with psychopathology and mothers with mood disorders. Girls in the CDA group reported more negative attachment with fathers, less perceived warmth, more overall rejection, more negative affect about their fathers, lower EA, and more negative communication than did girls in the NDA group. After controlling for marital status, depressed adolescents' scores of perceived maternal EA and negative affect towards mothers were comparable across the two groups. Fathers from the CDA and NDA groups did not differ in their ratings of warmth and rejection, but did report more negative communication with their adolescents compared to fathers of girls in the NDA group. Adolescents with depressed mothers reported more negative relationships with their fathers than adolescents with nondepressed mothers, indicating an important relationship between maternal depression and the father-adolescent relationship. In manuscript 2, investigation of the combined sample of depressed and nondepressed adolescents revealed that girls' perceptions of paternal EA and undifferentiated rejection predicted girls' depressive symptomatology above and beyond the presence of paternal psychopathology and maternal mood disorder. By adopting a multirater design, including extensive data on fathers and data on mothers, including clinical and nonclinical samples within one study, accounting for Axis I disorders together with depressive symptomatology, and including a balance of intact and single-parent families, this study addressed some of the gaps in the previous research. The findings of this thesis support taking an interpersonal and familial approach to treating depression in adolescents, addressing adolescents' perceptions of their relationships with both fathers and mothers.
Keywords: Psychology, Social.; Psychology, Clinical.